CULTURAL LITERACY THROUGH DOCUMENTARY FILM: THE BRAHMAN CEREMONY AS A MEDIUM FOR CULTURAL INHERITANCE - I Nyoman Payuyasa; I Made Denny Chrisna Putra; Ida Bagus Hari Kayana Putra (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2024)
Film can reflect the civilization of a country or nation. Through film works, one can clearly see the series of history, culture, philosophy, phenomena, and even social upheavals that have occurred from one era to another. Films, especially documentary films, also serve as powerful media for preserving cultural existence. The role of film in this era of globalization becomes an interesting study to present entertainment that can also serve as guidance for society. Especially considering the current situation of society living amidst the currents of global culture, which undoubtedly threatens the cultural heritage. The purpose of this research is to analyze the values of cultural literacy and the usefulness of the documentary film "Brahman Ceremony" as a medium for inheriting traditions. This research is qualitative descriptive research using observation and interview data collection methods. The results obtained through the documentary film titled "Brahman Ceremony" can serve as a means of socialization and education related to cultural literacy for the younger generation and the general public. The narrative in this documentary film provides an understanding of the process or ceremony of death packaged in a funeral ceremony for those who have become sulinggih, holy people, or priests in the Hindu belief. This process is interpreted as a tribute to the holy and unites them with Brahman. Cultural literacy can be seen from the explanations of religious and cultural anthropologists, sociologists of religion, and academics who provide an understanding of the organization of the ngaben ceremony or funeral rites. This film also contains cultural literacy in recorded history narrated well, especially related to the history of Sanur, the journey of Sanur's development into a famous tourist village known internationally. This journey is inseparable from the role of a figure named Ida Bagus Tjethana Putra or known as Ida Pedanda Gede Dwija Ngenjung.